Evaluating Nursing Interventions : a Theory-driven Approach. - Sidani, Dr. Souraya (SAGE Publications, 1997)
The authors of this innovative book offer a comprehensive perspective on nursing intervention together with theory-driven guidelines for future study. They provide a clear explanation of the problems encountered in outcomes and intervention research and then proceed, via the Intervention Theory, to show how these studies can be undertaken reasonably and comprehensively.